2017
DOI: 10.3389/fncel.2017.00164
|View full text |Cite
|
Sign up to set email alerts
|

Genetically-Informed Patient Selection for iPSC Studies of Complex Diseases May Aid in Reducing Cellular Heterogeneity

Abstract: Induced pluripotent stem cell (iPSC) technology is more and more used for the study of genetically complex human disease but is challenged by variability, sample size and polygenicity. We discuss studies involving iPSC-derived neurons from patients with Schizophrenia (SCZ), to exemplify that heterogeneity in sampling strategy complicate the detection of disease mechanisms. We offer a solution to controlling variability within and between iPSC studies by using specific patient selection strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…3d) 37,42,56,70,79,84,92 . Interestingly, it has been estimated that sample sizes of 10-30 individuals per hiPSC study may be required to achieve a statistical power of 80%, assuming that the cellular readouts variance is high and the disease effect is small (>0.7 relative heterogeneity, which is the ratio between within-group standard deviation and mean group difference) 189 . In this situation, most iPSC studies of PD may fall below the suggested sample size requirements.…”
Section: Studies Of Pd With Patient-derived Ipscsmentioning
confidence: 99%
“…3d) 37,42,56,70,79,84,92 . Interestingly, it has been estimated that sample sizes of 10-30 individuals per hiPSC study may be required to achieve a statistical power of 80%, assuming that the cellular readouts variance is high and the disease effect is small (>0.7 relative heterogeneity, which is the ratio between within-group standard deviation and mean group difference) 189 . In this situation, most iPSC studies of PD may fall below the suggested sample size requirements.…”
Section: Studies Of Pd With Patient-derived Ipscsmentioning
confidence: 99%
“…The larger the variance in the system, the bigger the needed sample size. Greater variance is typically associated with idiopathic versus genetically stratified cohorts, thus, in general, one would expect a larger sample size to be necessary for these studies [61]. For example, large, penetrant CNVs such as the 22q11.2 deletion often affect the expression of many genes within the CNV boundary [62].…”
Section: An Ideal Scenariomentioning
confidence: 99%
“…First, studies using related controls such as trio or quad designs that minimize genetic variation between ASD probands and controls may require smaller sample numbers compared with studies using unrelated controls in order to detect significant signal above background. Indeed, the selection of control individuals is equally as important as the selection of ASD patients in study design, and can influence the degree to which phenotypes are detected (or not detected) in a given assay [61]. As discussed below, this will require greater access to family-based ASD hPSC collections which are already widely utilized in genetic studies, to achieve statistical power with a more tenable number of samples.…”
Section: Strategies To Reduce Sample Sizementioning
confidence: 99%
“…B. Untersuchungen intermediärer Phänotypen für den genetischen Beitrag stratifiziert werden [13]. Aber auch im experimentellen Modell gibt es erste erfolgreiche Ansätze zur funktionellenAnalyse despolygenenBeitrags [20].…”
Section: Ausblickunclassified